Pelaksanaan Tanggung Jawab Oleh PT. Pos Terhadap Pengiriman Apabila Terjadi Kerusakan atau Keterlambatan (Studi Kasus PT.Pos Cabang Pekanbaru) - Irma Esterina Ginting; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Article 31 of Law Number 38 Year 2009 on Post stipulates that Post Operator must compensate for damages suffered by postal service users due to negligence and / or errors of postal organizer. Users of late package and mail delivery services obtain legal protection provided by PT. Postal items will be processed and provide compensation allowance in accordance with the rules applicable and in accordance with the decision of the Board of Directors. If the package and the letter is damaged or not up to the service user, PT. Post will give the responsibility to users of PT.Pos service but here the postal party neglected in his responsibility. The purpose of writing this thesis, namely: First, To know How the legal protection of users of packet delivery services at PT. Pekanbaru Branch Posts, Secondly, To find out what form of accountability is given by PT.Pos Indonesia Pekanbaru Branch if there is a claim from the user of the package delivery service PT.PosThis type of research can be classified in the type of research is a type of research that is sociological research on the effectiveness of the current law.From the results of the research the problem is clear that the legal protection of users of package delivery services at PT. Pekanbaru Branch Post is because it does not run smoothly and the number of negligence made by the post that can harm the postal service users themselves. On the postal service user who sends a letter or package that does not use express service, the estimated time of mail or package is within 7 days but the package has not reached within 7 days, the package is more than 7 days and not delivered to the package address Sent. Form of accountability provided by PT.Pos Indonesia Pekanbaru Branch if there is a claim from the user of the package delivery service PT.Pos is PT.Pos liability to the damage and delay of the package has not run smoothly which should be post if there is damage to the will be Process and provide compensation benefits in accordance with applicable rules and in accordance with the decision of the Board of Directors. If the package and the letter is damaged or not up to the service user, PT. Post will give the responsibility of the shipment will be replaced the cost of delay that is: 1 ½ x postage using Price Dependency Value of Goods (HTNB) and 1 x postage that does not use the Price. Keywords : Legal Protection-Accountability- PT.Pos-User Services